Mother and sibling interactions during the preweaning period influence myelination and impulse propagation of the sensory sural nerve in the adult rat. Issue 7 (29th August 2022) - Martínez‐Álvarez, Vladimir; Segura‐Alegría, Bertha; Rodríguez‐Torres, Erika Elizabeth; Porras, Mercedes Graciela; Aguirre‐Benítez, Elsa; González del Pliego, Margarita; Hudson, Robyn; Quiroz‐González, Salvador; Melo, Angel I.; Jiménez‐Estrada, Ismael
Abstract: To investigate whether mother and sibling interactions during the preweaning period influence the histological and electrophysiological characteristics of the sensory sural nerve (SUn) in the adult rat, litters composed of 1, 3, 6, 9, and 12 male pups (P) were formed and the pups routinely weighed until postnatal day 60 (PND60). At PND9, 3P and 6P litters showed greater body weight than pups without siblings or from 9P or 12P litters, and such differences in weight were maintained until adulthood. Analysis of maternal licking at PND8 and 9 showed that pups from large litters received fewer licks than pups from small size litters. At PND60, SUn of rats from 6P and 9P litters had greater compound action potential (CAP) amplitude and a higher proportion of axons with large myelin thickness than nerves from rats of 1P, 3P, or 12P litters. SUn of heaviest rats from 9P and 12P litters had greater CAP area and myelination than the lightest rats from the same litters. We propose that a complex interplay of sensory, social, and nutritional factors arising from mother and littermate interactions during the preweaning period influence myelination and the propagation of action potentials in the SUn of adult rats.